Do calcium supplements increase the risk of cardiovascular events? - Liew SM; Ng CJ (Malaysian Family Physician, 2013)
AssessMadam Chan, a 65-year-old retired staff nurse, walks into my clinic and asks for a refill of her prescription of losartan 50 mg daily and calcium carbonate 1200 mg daily. Her blood pressure is well controlled at 130/80 and she feels well otherwise. Examination and her annual investigation reports reveal no abnormalities.I remember the news of calcium supplements increasing the risk of cardiovascular events on BBC. Her bone mineral density scan, which was carried out a year ago, was normal. Madam Chan was started on calcium supplements by another doctor 5 years ago.